PROFITABILTAS SEBAGAI MODERATING PENGARUH KINERJA ESG, GREEN INNOVATION, ECO-EFFICIENCY TERHADAP NILAI PERUSAHAAN - Rahelliamelinda, Liangchui; Handoko, Jesica (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2024)
Firm that listed on the Indonesia Stock Exchange need to publishing sustainability reports at the end of their accounting period as a form of corporate environmental responsibility and concern in meeting the interests of stakeholders. This research aims to examine the effect of Environmental, Social and Governance performance, green innovation and eco-efficiency on firm value with profitability as the moderator. The object of this research is non-financial firm that listed on the Indonesia Stock Exchange and rated by Bloomberg for the 2020-2022 period. This research data was obtained from annual reports and company sustainability reports using purposive sampling techniques, resulting in a sample of 136 companies. Multiple linear regression analysis was used to process the data with the help of Statistical Product and Solutions version 25 software. The results of this research show that Environmental, Social and Governance performance has a positive effect, green innovation has no effect, while eco-efficiency has a negative effect on firm value. Profitability weakens the effect of Environmental, Social and Governance performance on firm value. On the contrary, profitability actually strengthens the effect of green innovation and eco-efficiency on firm value.